2016
DOI: 10.1097/mao.0000000000001199
|View full text |Cite
|
Sign up to set email alerts
|

Post Hybrid Cochlear Implant Hearing Loss and Endolymphatic Hydrops

Abstract: Objective To evaluate for potential causes of delayed loss of residual hearing that variably occurs with hybrid cochlear implants. Study design Histopathological evaluation of 29 human temporal bone (HTB) with cochlear implant. Setting The Neurotology and House HTB Laboratory of UCLA (House-UCLA). Subjects and methods HTB from cochlear implant patients from the House-UCLA HTB Laboratory (n = 28) and one courtesy of Massachusetts Eye and Ear Infirmary (MEEI). Histopathological analysis to identify the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…Animal studies support this notion in that RW insertions have been shown to result in less tissue formation, which correlated with better hearing outcomes . Postmortem temporal bone studies demonstrated that cochleostomy approaches were more likely to result in scala vestibuli fibrosis and endolymphatic hydrops when compared to RW insertions . The authors hypothesized that cochleostomies involving the scala vestibuli result in fibrosis of cochlear scala, leading to endolymphatic hydrops, which may be responsible for delayed hearing loss after cochlear implantation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Animal studies support this notion in that RW insertions have been shown to result in less tissue formation, which correlated with better hearing outcomes . Postmortem temporal bone studies demonstrated that cochleostomy approaches were more likely to result in scala vestibuli fibrosis and endolymphatic hydrops when compared to RW insertions . The authors hypothesized that cochleostomies involving the scala vestibuli result in fibrosis of cochlear scala, leading to endolymphatic hydrops, which may be responsible for delayed hearing loss after cochlear implantation.…”
Section: Discussionmentioning
confidence: 94%
“…37 Postmortem temporal bone studies demonstrated that cochleostomy approaches were more likely to result in scala vestibuli fibrosis and endolymphatic hydrops when compared to RW insertions. 38 The authors hypothesized that cochleostomies involving the scala vestibuli result in fibrosis of cochlear scala, leading to endolymphatic hydrops, which may be responsible for delayed hearing loss after cochlear implantation. In support of this theory, Quesnel et al described a patient who experienced delayed loss of residual hearing, and was found to have intrascalar fibrous tissue and new bone formation years after a cochleostomy approach.…”
Section: Factors Predictive Of Hearing Preservationmentioning
confidence: 99%
“…If the insertion involves the scala vestibuli it may cause fibrosis and ossification that blocks the ductus reuniens and result in a delayed endolymphatic hydrops because the endolymph passage from the cochlea to the saccule is blocked. 1 There was no relationship between speech understanding and the number of neurons. In fact, there was a slightly reversed association.…”
Section: Discussionmentioning
confidence: 98%
“…However, cochleostomy and related surgical approaches were found to be more associated with new bone formation and fibrotic tissue encapsulation of the electrode array due to larger initial intracochlear damage than RW, partly because they can lead to unintended involvement of scala vestibuli. 29 , 30 In fact, a direct comparison of perimodiolar arrays (Clarion TM or HiRes90K™) with a lateral wall array (Full-Band Straight) confirmed thickened fibrous capsule at the medial aspect of the electrode array in individuals implanted with a perimodiolar device. 31 This finding was attributed to closer proximity to the modiolus and differences in the shape of electrical field.…”
Section: Discussionmentioning
confidence: 98%